Problem of Raising Pulpwood Plantations for Nepanagar Paper Mill - Deshmukh, D. K.; Yadav, J. S. P. (Indian Forester, 1965)
The problem of anticipated shortage in the future supply of raw material for the National News Print Ltd. Nepanagar (Madhya Pradesh) has been discussed. The causes of past failures in raising plantations have been analysed and the urgent necessity for planting appropriate fast growing species to meet the demand of the Mill has been elucidated. A brief account has been given of the locality factors including climate and soil characteristics together with general moisture regime calculated for the area. A tentative classification of soils found in the tract has been presented and proper selection of sites and species fOr ensuring success has been explained. The various soil working methods, planting techniques and moisture conservtaion practices suitable for the locality have been described. Certain items of future research to achieve these objectives have also been suggested.